2021
DOI: 10.1101/2021.12.08.471763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The p97-UBXD8 complex modulates ER-Mitochondria contact sites by modulating membrane lipid saturation and composition

Abstract: The intimate association between the endoplasmic reticulum (ER) and mitochondrial membranes at ER-mitochondria contact sites serves as a platform for several critical cellular processes, in particular lipid synthesis. Enzymes involved in lipid biosynthesis are enriched at contacts and membrane lipid composition at contacts is distinct relative to surrounding membranes. How contacts are remodeled and the subsequent biological consequences of altered contacts such as perturbed lipid metabolism remains poorly und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…However, the mechanism by which this occurs is not known. VCP and the ERAD adaptor, UBXD8 regulate ER-mitochondria contacts by regulating membrane lipid saturation and composition ( Figure 2C ) [ 71 ]. VCP–UBXD8 regulates contacts by modulating the expression of the fatty acid desaturase SCD1 through the SREBP1 pathway.…”
Section: Regulation Of Er-mitochondrial Membrane Contact Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the mechanism by which this occurs is not known. VCP and the ERAD adaptor, UBXD8 regulate ER-mitochondria contacts by regulating membrane lipid saturation and composition ( Figure 2C ) [ 71 ]. VCP–UBXD8 regulates contacts by modulating the expression of the fatty acid desaturase SCD1 through the SREBP1 pathway.…”
Section: Regulation Of Er-mitochondrial Membrane Contact Sitesmentioning
confidence: 99%
“…Loss of VCP–UBXD8 stabilizes INSIG1, inactivating SREBP1, and decreasing SCD1 transcript and protein levels. This, in turn, leads to an increase in membrane saturation thereby stabilizing contacts ( Figure 2C ) [ 71 ]. This new function of VCP appears to be relevant in the context of disease.…”
Section: Regulation Of Er-mitochondrial Membrane Contact Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The TMT-based proteomics was performed exactly as previously described 85 . Briefly, 100 µg protein of each sample was obtained by cell lysis in lysis buffer (8 M Urea, 200 mM N-(2-Hydroxyethyl)piperazine-N′-(3-propanesulfonic acid) (EPPS) pH 8.5) followed by reduction using 5 mM tris(2-carboxyethyl)phosphine (TCEP), alkylation with 14 mM iodoacetamide and quenched 33 using 5 mM dithiothreitol.…”
Section: Sample Preparation Digestion and Tandem-mass Tag (Tmt) Labelingmentioning
confidence: 99%
“…Over 40 adaptors have been identified that enable p97 recruitment to ubiquitylated substrates 5 . We and others have shown that p97-adaptor complexes are important for a large number of cellular processes including organelle contact sites 6 , cell cycle regulation 7 , DNA damage response 8 , and autophagy 9 (see 9,10 for review). As a result, loss of p97 impacts the degradation of a large cohort of the ubiquitin-modified proteome.…”
Section: Introductionmentioning
confidence: 99%